The implicit daisy-chaining property of constrained predictive control - Maciejowski, Jan M. (Zielona Góra: Uniwersytet Zielonogórski)
Systems with redundant control actuators are sometimes arranged so that a new actuator comes into play if the one normally used becomes saturated. We call this 'daisy-chaining'. Such an arrangement also provides a degree of fault-tolerance against actuator failures.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka